Risiko Pendapatan Dan Perilaku Petani Terhadap Risiko Pada Usahatani Pepaya California Di Dataran Tinggi Kabupaten Purworejo - Istiko Agus Wicaksono; Dyah Panuntun Utami (Universitas Muhammadiyah Purworejo, 2016)
This study aims to determine: (1) the amount of production and income of California papaya farming; (2) the magnitude of the risk of production and income risk of California papaya farming; (3) farmer's behavior in facing the risk of California papaya farming income. The method used in this research is the descriptive method with the research location selected Cepedak Village, Bruno District. The number of research samples was 48 farmers who cultivated California papayas and at least harvested the papaya once. The research data were obtained using the method of observation, interviews, recording, and documentation. The results showed that the average production of the California papaya was 9109 kilograms. The average income of California papaya farming is IDR 19,585,850.00. The risk of California papaya farming production was 19.75% and the income risk of California papaya farming was 18.83%. The risk of production and income of California papaya farming is in the low-risk category because the CV value is <1 (production CV is 0.197 and income CV is 0.188). California papaya farmers have 25 risk lover behavior (52.08%), 19 risk-neutral behavior (39.58%), and 4 risk averter behavior (8.34%). This shows that most of the California papaya farmers have risk lover behavior in taking risks.